Hungarian wine marketing ang wine consumption - Kiss, Klára (Acta Agraria Debreceniensis, 2012)
Hungarian wine is not in such a bad position as it is considered. We have outstanding specialists and the country’s natural conditions are also proper. The level of Hungarian wone culture is comparatively low but is capable of progress. Hungarian Wine Marketing Non-profit Company helps public wine marketing to be really effective. The development of tourism in wine-growing regions and advertising would considerably promote the popularity of Hungarian wine.